It's All Triples 2

Geometry Level 4

Let p p be a positive even integer.

Given area A 1 = 60 A_{1} = 60 , find the distance d 2 d_{2} above.


The answer is 10517.65850528.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Jun 10, 2018

This problem was created using a general recursive sequence that I derived using primitive pythagorean triples.

Below is the recursive sequence.

Let

a 1 = m 1 2 + n 1 2 a_{1} = m_{1}^2 + n_{1}^2

b 1 = 2 m 1 n 1 b_{1} = 2m_{1}n_{1}

c 1 = m 1 2 + n 1 2 c_{1} = m_{1}^2 + n_{1}^2 ,

where ( m 1 , n 1 ) = 1 , m 1 > n 1 (m_{1},n_{1}) = 1, m_{1} > n_{1} and m 1 m_{1} is even and n 1 n_{1} is odd.

for ( 1 j n 1 ) (1 \leq j \leq n - 1) let

a j + 1 = c j a_{j + 1} = c_{j}

b j + 1 = ( c j + 1 ) ( c j 1 ) 2 b_{j + 1} = \dfrac{(c{j} + 1)(c_{j} - 1)}{2}

c j + 1 = c j 2 + 1 2 c_{j + 1} = \dfrac{c_{j}^2 + 1}{2}

then for each ( 1 k n ) ( a k , b k , c k ) (1 \leq k \leq n) \:\ (a_{k},b_{k},c_{k}) is a primitive pythagorean triple.

Let p p be a positive even integer with m 1 = p m_{1} = p and n 1 = 1 n_{1} = 1 .

Using the above the first ppt triple is ( p 2 1 , 2 p , p 2 + 1 ) A 1 = 1 2 ( 2 p ) ( p 2 1 ) = 60 p 3 p 60 = 0 ( p 4 ) ( p 2 + 4 p + 15 ) = 0 p = 4 (p^2 - 1,2p,p^2 + 1) \implies A_{1} = \dfrac{1}{2}(2p)(p^2 - 1) = 60 \implies p^3 - p - 60 = 0 \implies (p - 4)(p^2 + 4p + 15) = 0 \implies p = 4

( p 2 1 , 2 p , p 2 + 1 ) = ( 15 , 8 , 17 ) \implies (p^2 - 1,2p,p^2 + 1) = (15,8,17) .

The second ppt triple is ( p 2 + 1 , ( p 2 + 2 ) p 2 2 , p 4 + 2 p 2 + 2 2 ) = ( 17 , 144 , 145 ) (p^2 + 1,\dfrac{(p^2 + 2)*p^2}{2},\dfrac{p^4 + 2p^2 + 2}{2}) = (17,144,145)

The third ppt triple is ( p 4 + 2 p 2 + 2 2 , p 2 ( p 2 + 2 ) ( p 4 + 2 p 2 + 4 ) 8 , p 8 + 4 p 6 + 8 p 4 + 8 p 2 + 8 8 ) = ( 145 , 10512 , 10513 ) (\dfrac{p^4 + 2p^2 + 2}{2}, \dfrac{p^2(p^2 + 2)(p^4 + 2p^2 + 4)}{8}, \dfrac{p^8 + 4p^6 + 8p^4 + 8p^2 + 8}{8}) = (145,10512,10513) .

cos ( θ 1 ) = 8 17 , sin ( θ 1 ) = 15 17 \cos(\theta_{1}) = \dfrac{8}{17}, \sin(\theta_{1}) = \dfrac{15}{17}

cos ( θ 2 ) = 17 145 , sin ( θ 2 ) = 144 145 \cos(\theta_{2}) = \dfrac{17}{145}, \sin(\theta_{2}) = \dfrac{144}{145}

cos ( θ 3 ) = 145 10513 , sin ( θ 3 ) = 10512 10513 \cos(\theta_{3}) = \dfrac{145}{10513}, \sin(\theta_{3}) = \dfrac{10512}{10513}

cos ( θ 1 + θ 2 + θ 3 ) = \implies \cos(\theta_{1} + \theta_{2} + \theta_{3}) =

cos ( θ 1 ) cos ( θ 2 ) cos ( θ 3 ) sin ( θ 1 ) sin ( θ 2 ) cos ( θ 3 ) sin ( θ 1 ) sin ( θ 3 ) cos ( θ 2 ) sin ( θ 2 ) sin ( θ 3 ) cos ( θ 1 ) = \cos(\theta_{1})\cos(\theta_{2})\cos(\theta_{3}) - \sin(\theta_{1})\sin(\theta_{2})\cos(\theta_{3}) - \sin(\theta_{1})\sin(\theta_{3})\cos(\theta_{2}) - \sin(\theta_{2})\sin(\theta_{3})\cos(\theta_{1}) =

8 10513 ( 15 ) ( 144 ) ( 17 ) ( 10513 ) ( 15 ) ( 10512 ) ( 10513 ) ( 145 ) ( 144 ) ( 10512 ) ( 8 ) ( 145 ) ( 10513 ) ( 17 ) = 15083864 25914545 \dfrac{8}{10513} - \dfrac{(15)(144)}{(17)(10513)} - \dfrac{(15)(10512)}{(10513)(145)} - \dfrac{(144)(10512)(8)}{(145)(10513)(17)} = -\dfrac{15083864}{25914545}

\implies

d 2 = A E = 8 2 + 1051 3 2 + ( 2 ) ( 8 ) ( 10513 ) ( 15083864 ) 25914545 = 272681111169 2465 10517.65850528 d_{2} = AE = \sqrt{8^2 + 10513^2 + \dfrac{(2)(8)(10513)(15083864)}{25914545}} = \sqrt{\dfrac{272681111169}{2465}} \approx \boxed{10517.65850528} .

Note: For the general recursive sequence above the sum of the squares a 1 2 + j = 1 n b j 2 = c n 2 a_{1}^2 + \sum_{j = 1}^{n} b_{j}^2 = c_{n}^2 .

For this problem with p = 4 p = 4 we have: 1 5 2 + 8 2 + 14 4 2 + 1051 2 2 = 1051 3 2 . 15^2 + 8^2 + 144^2 + 10512^2 = 10513^2.

Also note given ( a 1 , b 1 , c 1 ) (a_{1},b_{1},c_{1}) and setting m j + 1 n j + 1 = 1 m_{j + 1} - n_{j + 1} = 1 and m j + 1 + n j + 1 = c j m j + 1 = c j + 1 2 m_{j + 1} + n_{j + 1} = c_{j} \implies m_{j + 1} = \dfrac{c_{j} + 1}{2} and n j + 1 = c j 1 2 n_{j + 1} = \dfrac{c_{j} - 1}{2} and replacing m j + 1 , n j + 1 m_{j + 1},n_{j + 1} into a j + 1 = ( m j + 1 n j + 1 ) ( m j + 1 + n j + 1 ) , b j + 1 = 2 m j + 1 n j + 1 , c j + 1 = ( m j + 1 ) 2 + ( n j + 1 ) 2 a_{j + 1} = (m_{j + 1} - n_{j + 1})(m_{j + 1} + n_{j + 1}), \:\ b_{j + 1} = 2m_{j + 1}n_{j + 1}, \:\ c_{j + 1} = (m_{j + 1})^2 +(n_{j + 1})^2

\implies

a j + 1 = c j a_{j + 1} = c_{j}

b j + 1 = ( c j + 1 ) ( c j 1 ) 2 b_{j + 1} = \dfrac{(c_{j} + 1)(c_{j} - 1)}{2}

c j + 1 = c j 2 + 1 2 c_{j + 1} = \dfrac{c_{j}^2 + 1}{2}

and for each j j such that ( 1 j n ) c j (1 \leq j \leq n) \:\ c_{j} is odd a j , b j \implies a_{j},b_{j} and c j c_{j} are positive integers and ( c j , c j 2 1 2 , c j 2 1 2 + 1 ) = 1 (c_{j}, \dfrac{c_{j}^2 - 1}{2}, \dfrac{c_{j}^2 - 1}{2} + 1) = 1 and a j 2 + b j 2 = c j 2 a_{j}^2 + b_{j}^2 = c_{j}^2 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...